2019
DOI: 10.1308/rcsann.2018.0158
|View full text |Cite
|
Sign up to set email alerts
|

Combined ultrasound and Sestamibi scintigraphy provides accurate preoperative localisation for patients with primary hyperparathyroidism

Abstract: Introduction Minimally invasive parathyroidectomy has advantages over the traditional bilateral neck exploration for the surgical treatment of primary hyperparathyroidism. It requires accurate localisation of the parathyroid pathology prior to surgery. The best method of preoperative localisation in a district general hospital setting is not well understood. Methods All patients who underwent parathyroidectomy for primary hyperparathyroidism from 2008 to 2016 were identified from a prospectively maintained dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
(45 reference statements)
2
17
0
3
Order By: Relevance
“…Similar results were seen in a recent study from China, which showed US sensitivity ranging from 90.70% for parathyroid adenoma to 93.5% for parathyroid hyperplasia [15]. Scattergood et al reported that US had higher sensitivity than 99m-Tc sestamibi scintigraphy [16]. Interestingly, a recent study regarding parathyroid carcinoma localization reported the sensitivity and accuracy of US to be 80% and 73% respectively, of 4-D CT to be 79% and 82%, and of 99m-Tc sestamibi to be 81% and 78% [17].…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were seen in a recent study from China, which showed US sensitivity ranging from 90.70% for parathyroid adenoma to 93.5% for parathyroid hyperplasia [15]. Scattergood et al reported that US had higher sensitivity than 99m-Tc sestamibi scintigraphy [16]. Interestingly, a recent study regarding parathyroid carcinoma localization reported the sensitivity and accuracy of US to be 80% and 73% respectively, of 4-D CT to be 79% and 82%, and of 99m-Tc sestamibi to be 81% and 78% [17].…”
Section: Discussionsupporting
confidence: 82%
“…4 In cases with concordance, both imaging tools provide a sensitivity of approximately 88%. Currently, preoperative key imaging tools for localizing parathyroid adenomas include ultrasound and sestamibi scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, preoperative key imaging tools for localizing parathyroid adenomas include ultrasound and sestamibi scanning. 4 In cases with concordance, both imaging tools provide a sensitivity of approximately 88%. 4 Nonlocalizing parathyroid adenomas on imaging studies can represent a clinical challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations